ChemInform Abstract: Callyspongisines A—D: Bromopyrrole Alkaloids from an Australian Marine Sponge, Callyspongia sp. Issue 27 (8th July 2014) - Plisson, Fabien; Prasad, Pritesh; Xiao, Xue; Piggott, Andrew M.; Huang, Xiao‐cong; Khalil, Zeinab; Capon, Robert J.
Abstract isolation, structure and bioactivity